Emerging PD-1/PD-L1 antagonists for the treatment of malignant melanoma. (3rd April 2021) - Vanella, Vito; Festino, Lucia; Vitale, Maria Grazia; Alfano, Benedetta; Ascierto, Paolo Antonio
ABSTRACT: Introduction: Increased understanding of the interactive mechanisms between tumors and the immune system led to the development of immune checkpoint inhibitors, which have revolutioned the treatment of metastatic melanoma and subsequently many other tumors. In 2014, nivolumab and pembrolizumab, two checkpoint inhibitors binding to PD-1, were approved for the treatment of metastatic melanoma. Since then, a plethora of new molecules have enriched the armamentarium against melanoma. Areas covered: This review summarizes the last updates about treatment with nivolumab and pembrolizumab, data on other PD-1/PDL-1 agents such as spartalizumab and atezolizumab and emerging compounds, new combinations with NKTR-214, anti LAG-3, anti IDO-1 and TVEC, new checkpoint inhibitors (e.g. TIM-3 or TIGIT) and other new molecules for the treatment of metastatic melanoma. Expert opinion: Currently, several ongoing clinical trials are investigating novel molecules, or immunotherapy combinations, in order to achieve even better survival outcomes for patients, overcoming resistance mechanisms and improving toxicity profiles. The challenge in the near future will be to select the most appropriate treatments according to the specific characteristics of the patients.